Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Does GMAT RC seem like an uphill battle? e-GMAT is conducting a free webinar to help you learn reading strategies that can enable you to solve 700+ level RC questions with at least 90% accuracy in less than 10 days.

Attend a Veritas Prep GMAT Class for Free. With free trial classes you can work with a 99th percentile expert free of charge. Learn valuable strategies and find your new favorite instructor; click for a list of upcoming dates and teachers.

I could solve it by plugging numbers. But I am looking for the algebraic way to solve this equation.

Hi, and welcome to the Gmat Club. Below is algebraic solution for you question:

Guess the question must be \(\frac{p+5+p^3(-p-5)}{-p-5}=?\)

If yes than: \(\frac{p+5+p^3(-p-5)}{-p-5}=\frac{-(-p-5)+p^3(-p-5)}{-p-5}\) --> factor out \((-p-5)\) --> \(\frac{-(-p-5)+p^3(-p-5)}{-p-5}=\frac{(-p-5)(-1+p^3)}{-p-5}=-1+p^3=p^3-1\).

So we're looking for an answer that = 7 when P = 2

Answer A: 2 + 5 + 8 = 15 NOT a match Answer B: 8 + 5 = 13 NOT a match Answer C: 8 NOT a match Answer D: 8 - 1 = 7 This IS a MATCH Answer E: 8 - 5 = 3 NOT a match

You're going to face some GMAT questions on Test Day that 'test' you on concepts that you know, but in ways that you're probably not used to thinking about. If you choose to approach this question algebraically (which is an approach that you do not have to use), then you would find that factoring the given equation can help to simplify it. You probably already know how to factor...

For example: 2X + 4 can be factored down to 2(X +2).

In that same way, you can factor out other common 'pieces':

-2X - 10 can be factored down to -2(X + 5).

The concept of 'factoring out a negative' is what mcdude123 used:

-P + 5 can be factored down to -1(P+5). At that point, you can then factor out (P+5) out of the numerator of the fraction.

Hi, and welcome to the Gmat Club. Below is algebraic solution for you question:

Guess the question must be p+5+p3(−p−5)−p−5=?p+5+p3(−p−5)−p−5=?

If yes than: p+5+p3(−p−5)−p−5=−(−p−5)+p3(−p−5)−p−5p+5+p3(−p−5)−p−5=−(−p−5)+p3(−p−5)−p−5 --> factor out (−p−5)(−p−5) --> −(−p−5)+p3(−p−5)−p−5=(−p−5)(−1+p3)−p−5=−1+p3=p3−1−(−p−5)+p3(−p−5)−p−5=(−p−5)(−1+p3)−p−5=−1+p3=p3−1.

Answer: D.

Hope it helps.

Hi Brent,

Can you explain what you did after factoring (-p-5)?

Hi, and welcome to the Gmat Club. Below is algebraic solution for you question:

Guess the question must be p+5+p3(−p−5)−p−5=?p+5+p3(−p−5)−p−5=?

If yes than: p+5+p3(−p−5)−p−5=−(−p−5)+p3(−p−5)−p−5p+5+p3(−p−5)−p−5=−(−p−5)+p3(−p−5)−p−5 --> factor out (−p−5)(−p−5) --> −(−p−5)+p3(−p−5)−p−5=(−p−5)(−1+p3)−p−5=−1+p3=p3−1−(−p−5)+p3(−p−5)−p−5=(−p−5)(−1+p3)−p−5=−1+p3=p3−1.

Answer: D.

Hope it helps.

Hi Brent,

Can you explain what you did after factoring (-p-5)?

cancelled it from numerator and denominator to get -1+p^3. Maybe the absence of parenthesis in the denominator confused you? -p-5 in denominator is the same as (-p-5)

You're going to find that most GMAT questions can be approached in more than one way. As such, if you don't understand one particular approach to a question, then there's a pretty good chance that there will be another approach that you mind find easier to deal with. In my approach (above), I chose to TEST VALUES:

IF..... P = 2 Then the calculation becomes....

[2 + 5 + 8(-7)] / (-7)

[7 - 56]/(-7) [-49]/(-7) = 7

So we're looking for an answer that = 7 when P = 2

Answer A: 2 + 5 + 8 = 15 NOT a match Answer B: 8 + 5 = 13 NOT a match Answer C: 8 NOT a match Answer D: 8 - 1 = 7 This IS a MATCH Answer E: 8 - 5 = 3 NOT a match

A. p+5 + p^3 B. P^3 + 5 C. p^3 D. p^3 - 1 E. p^3 - 5

Let's just focus on the NUMERATOR for a second. Given: p + 5 + p³(-p - 5) Factor -1 from the first part to get: -1(-p - 5) + p³(-p - 5) So, we now have: -1(-p - 5) + p³(-p - 5) Combine terms to get: (-1 + p³)(-p - 5) Rearrange terms to get: (p³ - 1)(-p - 5)

Now replace ORIGINAL numerator with (p³ -1)(-p - 5) We get: (p³ - 1)(-p - 5)/(-p - 5) Simplify to get: (p³ - 1) Answer: D

We're looking for an expression that is equivalent to the original expression. So if we evaluate the original expression for a particular value of p, then the equivalent expression should also yield the same value when we plug in the same value of p. Let's test p = 1

Take: [p + 5 + p³(-p - 5)]/[-p - 5] Replace p with 1 to get: [1 + 5 + 1³(-1 - 5)]/[-1 - 5] Evaluate to get: 0/-6, which equals 0

So, when p = 1, the original express evaluates to be 0 Now let's plug p = 1 into the answer choices.... A. 1 + 5 + 1^3 = 7. No good, we want 0. ELIMINATE. B. 1^3 + 5 = 6. No good, we want 0. ELIMINATE. C. 1^3 = 1. No good, we want 0. ELIMINATE. D. 1^3 - 1 = 0. Great - KEEP E. 1^3 - 5 = -4. No good, we want 0. ELIMINATE.

I think people are are confused with the format as it's a bit foreign and people are wrongly eliminating the −p−5 from both the top and bottom.

Essentially the question is \(\frac{1+2+3(x)}{x}\) in which simplified would be \(\frac{1}{x}\)+ \(\frac{2}{x}\)+ \(\frac{3}{1}\) (cancelling the x's in 3x/x.

And not \(\frac{(1+2+3)x}{x}\) Here, you can eliminate the x's and get 1+2+3

There are a few ways to do this question. I chose the simplification/elimination (however you call it) method since I could see some symmetry in the question. Else I would have also gone for value substitution.